2024
DOI: 10.1111/raq.12912
|View full text |Cite
|
Sign up to set email alerts
|

Nitrogen cycling process and application in different prawn culture modes

Zhao Chen,
Jian Li,
Qianqian Zhai
et al.

Abstract: Nitrogenous waste is a global concern in aquatic ecosystems. In the shrimp farming system, feeding is the main input of nitrogen, which leads to the accumulation of nitrogenous waste, such as ammonia, nitrite, and nitrate. Nitrogen cycling is crucial for nitrogenous waste removal and for the stability of the aquaculture system. Under the action of different functional microorganisms, a variety of nitrogen cycling pathways can be used for the transformation and removal of nitrogenous waste. Understanding the co… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2024
2024
2025
2025

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 270 publications
0
1
0
Order By: Relevance
“…This augmented abundance of Bacillus can be explained via the integration of dietary factors. Also, this may be due, to some extent, to the fact that greenhouse culture belongs to autotrophic biofloc farming [6,27]. Some studies have found that a similar community composition exists in biofloc culture systems, such as Proteobacteria and Bacillus.…”
Section: Analysis Of Dynamic Changes Of Gut Microbial Communitymentioning
confidence: 99%
“…This augmented abundance of Bacillus can be explained via the integration of dietary factors. Also, this may be due, to some extent, to the fact that greenhouse culture belongs to autotrophic biofloc farming [6,27]. Some studies have found that a similar community composition exists in biofloc culture systems, such as Proteobacteria and Bacillus.…”
Section: Analysis Of Dynamic Changes Of Gut Microbial Communitymentioning
confidence: 99%